2020
DOI: 10.1007/s00467-020-04731-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of isolated systolic hypertension with normal central blood pressure in adolescents—prospective study

Abstract: Background The clinical significance of isolated systolic hypertension with normal central blood pressure known as spurious hypertension (sHT) in adolescents and its evolution over time is not known. Methods The aim of this study was to analyze changes in office, ambulatory blood pressure (ABPM), central systolic blood pressure (cSBP), hemodynamic parameters, and target organ damage (TOD) over a 1-year follow-up in a group of non-obese children with sHT. Results Of 294 patients referred for primary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The observations suggest that spurious hypertension may not be a benign condition, as was previously suggested [3,4,31]. The results of a recent prospective study, which showed that after 12 months, 23% of pediatric patients with sHTN developed sustained hypertension with elevated cSBP, also speak against the benign nature of sHTN [6].…”
Section: Cardiac Hypertension-mediated Organ Damage and Aortic Stiffn...mentioning
confidence: 58%
See 1 more Smart Citation
“…The observations suggest that spurious hypertension may not be a benign condition, as was previously suggested [3,4,31]. The results of a recent prospective study, which showed that after 12 months, 23% of pediatric patients with sHTN developed sustained hypertension with elevated cSBP, also speak against the benign nature of sHTN [6].…”
Section: Cardiac Hypertension-mediated Organ Damage and Aortic Stiffn...mentioning
confidence: 58%
“…Moreover, some adolescents and young adults with ISH present with normal central SBP (cSBP) and hence it was hypothesized that this form of ISH may not be associated with increased cardiovascular risk and was therefore called spurious hypertension (sHTN) [3]. The clinical impact and proper management of ISH and sHTN remain controversial, with several studies showing contradictory results [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence in CYP with primary hypertension, however, remains limited. A recent study observed a decrease in BP and cfPWV z score (but not absolute values of cfPWV) in children over a 12-month period of nonpharmacological therapy [63]. Similarly, a BPindependent regression of cIMT and of CWSA, was observed in pediatric studies [32].…”
Section: Discussionmentioning
confidence: 89%
“…Secondly, what is at least the short-term outcome of patients with spurious hypertension? The data by Obrycki et al suggest that some of these individuals progress towards true hypertension with elevated CBP [20]. Moreover, the same group recently revealed that even patients with normal central blood pressure may have left ventricular hypertrophy [21], questioning whether "spurious" ISH is actually a benign condition.…”
Section: Discussionmentioning
confidence: 99%